Pengaruh dan Faktor Penentu Peningkatan Kualitas Proyek dalam Perspektif Manajemen Proyek Modern - Dinda Putri Rezeki; Habibi Habibi; Zuhair Mubarrak Hazaa; Amiruddin Siahaan (Medan Resource Center, 2025)
This study examines the influence of Project Management Competence, Agile Methodology, and Digital Technology on Project Quality within the framework of modern project management. The research is motivated by the growing organizational demand to enhance project success through strengthened human resource competencies, adaptive working methodologies, and effective digital transformation. Employing a quantitative approach, the study utilizes Structural Equation Modeling to analyze the relationships among the proposed variables. The goodness-of-fit indices indicate that the structural model meets acceptable criteria, as reflected by Chi-square/df = 2.347, RMSEA = 0.073, GFI = 0.918, AGFI = 0.902, CFI = 0.935, and TLI = 0.928. The findings reveal that all independent variables exert positive and statistically significant effects on project quality. Project Management Competence demonstrates the strongest influence (? = 0.412), followed by Agile Methodology (? = 0.367) and Digital Technology (? = 0.289). These variables collectively enhance project quality by improving planning effectiveness, execution flexibility, and efficiency in control and monitoring processes. The study argues that the integration of managerial competence, Agile practices, and digital technologies constitutes a critical determinant of high-quality project outcomes, offering strategic implications for organizations seeking to strengthen modern project management performance.